Screening of anticancer activities from agarwood's Methanol extract (gyrinops verstegii [gilg.] Domke) - TOTOK K. WALUYO,; G. PASARIBU, (International Journal of Pharma and Bio Sciences, 2017)
Agarwood typifies as one of non-wood forest products with high values. It is a resin entity, contained/embedded in woods of e.g. Aquilaria spp. and Gyrinops spp, under Thymelaeaceae family. Gyrinops species serves as Indonesia’s endemic plants and currently has been numerously planted/cultivated particularly in Eastern Indonesia’s part. The research was conducted on Gyrinops verstegii species which aimed to look into possible uses of its agarwood, obtained through methanol extraction, for anticancer agent. Agarwood for such extraction presented the lowest quality based on the Indonesia’s National Standards. The obtained agarwood’s methanol extract was used for the screening-ability test to inhibit growth of MCF-7’s breast cancer cells (ATCC HTB 22) that used MTT assay methods. IC50 values for agarwood extract ranged about 5.01-8.32 µg/mL, regarded effective for such inhibition. These prospective results can become a significant basis to further develop alternative efficacious drugs against cancer diseases.